Impact of Nutritional Status on Gastroenteropancreatic Neuroendocrine Tumors (GEP-NET) Aggressiveness - Barrea, Luigi; Altieri, Barbara; Muscogiuri, Giovanna; Laudisio, Daniela; Annunziata, Giuseppe; Colao, Annamaria; Faggiano, Antongiulio; Savastano, Silvia (Nutrients, 2018)
Neuroendocrine tumors (NETs) are rare neoplasms mostly originating from the gastroenteropancreatic tract (GEP-NETs). Data regarding nutritional status in GEP-NET patients are limited. The aim of the study was to investigate the nutritional status and adherence to the Mediterranean Diet (MD) in GEP-NET patients and to correlate them with tumor aggressiveness. A cross-sectional case-control observational study was conducted enrolling 83 patients with well-differentiated G1/G2 GEP-NETs after resection, as well as 83 healthy subjects, age, sex and body mass index-matched. Nutritional status was assessed by evaluating with Bioelectrical Impedance analysis and its phase angle (PhA), adherence to the MD according to PREDIMED score, dietary assessment, anthropometric parameters, and clinico-pathological characteristics. GEP-NET patients consumed less frequently vegetables, fruits, wine, fish/seafood, nuts, and more frequently red/processed meats, butter, cream, margarine, and soda drinks than controls. Patients with more aggressive disease presented a lower adherence to MD according to PREDIMED categories in comparison to G1, localized and free/stable disease status. A smaller PhA value and a lower PREDIMED score were significantly correlated with G2 tumor, metastases, and progressive disease. To the best of our knowledge, this is the first study reporting an association between nutritional status and tumor aggressiveness in a selected group of GEP-NETs. Moreover, higher intakes of food of MD, may represent a potential tool for prevention of tumor aggressiveness. Thus, a skilled nutritionist should be an integral part of the multidisciplinary management of GEP-NET patients.